Sistem Informasi Modeling Kawasan Rawan Longsor Berbasis 3 Dimensi - Agussalim Patola DM; Raden Wirawan; Afandi, Afandi (Ikatan Ahli Informatika Indonesia, 2023)
The high level of losses experienced by the community caused by natural disasters is due to the lack of information obtained by the community about possible disasters that occur around it. In dealing with disasters can be done by utilizing various kinds of the latest technology such as the use of drone technology for data collection that can reach disaster areas. The purpose of this study is to model the information system of landslide-prone areas from drone photos in 3 dimensions. . The method used is photogrammetry by taking ortho photos using a mavic 2 pro type drone and secondary data of the soil layer from sondir at the location of Sapaya road, Bungaya District, Gowa Regency, South Sulawesi. The results are known that from 3-dimensional modeling it can be seen that the soil contour and the degree of slope for each area at the location are between 320 – 520 with a safe factor value below 1. Furthermore, it also appears that the location of rainwater flows can be a trigger factor for landslides so that this information can be the initial data in increasing awareness of potential landslide disasters.